Force-velocity-power profiling of maximal effort sprinting, jumping and hip thrusting: Exploring the importance of force orientation specificity for assessing neuromuscular function - Junge, N.; Lundsgaard, A.; Hansen, M. F.; Samozino, P.; Morin, J.-B.; Aagaard, P.; Contreras, B.; Nybo, L. (Journal of Sports Sciences, 2021)
Comprehensive information regarding neuromuscular function, as assessed through force-velocity-power (FVP) profiling, is of importance for training optimization in athletes. However, neuromuscular function is highly task-specific, potentially governed by dissimilarity of the overall orientation of forceapplication. The hip thrust (HT) exercise is thought to be of relevance for sprinting considering its antero-posterior force orientation and considerable hip-extensor recruitment, however, the association between their respective FVP profiles remains unexplored. Therefore, to address the concept of force orientation specificity within FVP profiling, the maximal theoretical neuromuscular capabilities of 41 professional male footballers (22.1 ± 4.1 years, 181.8 ± 6.4 cm, 76.4 ± 5.5 kg) were assessed during sprint acceleration, squat jumping (SJ) and the HT exercise. No significant associations were observed for maximal theoretical force or velocity between the three FVP profiling modalities, however, maximal theoretical power (Pmax) was correlated between sprinting and SJ (r = 0.73, P < 0.001) and HT and SJ (r = 0.44, P = 0.01), but not between sprinting and HT (r = 0.18, P = 0.36). In conclusion, although Pmax may be considered a somewhat universal lower-extremity capability, neuromuscular function is associated with substantial task-specificity not solely governed by the overall direction of force orientation.